Enzymes : glycosylphosphatidylinositol (GPI) anchoring of proteins. (Enzymes, 2009)
This volume of The Enzymes features high-caliber thematic articles on the topic of glycosylphopshatidylinositol (GPI) anchoring of proteins. * Contributions from leading authorities * Informs and updates on all the latest developments in the field.